2021
DOI: 10.3390/w13070891
|View full text |Cite
|
Sign up to set email alerts
|

Understanding China’s Urban Rainstorm Waterlogging and Its Potential Governance

Abstract: Urban rainstorm waterlogging is one of the most important problems in urban development and a comprehensive embodiment of urban diseases. China is facing a severe risk of rainstorm waterlogging disasters, which is affecting sustainable development. Urban rainstorm waterlogging in China is caused by many factors, including natural factors and human factors, such as climate warming, unreasonable urban construction, inadequate upgrading of urban fortification standards, etc. Based on the analysis of the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…According to the 2006-2018 China Water and Drought Disaster Bulletin statistics [13], China has been flooded in more than 100 cities every year since 2006, including 258 cities flooded in 2010, 184 in 2012, and 234 in 2013. According to the special research on 351 cities by the Ministry of Housing and Urban-Rural Development of the People's Republic of China [15], 62% of the cities in China had pluvial flooding from 2008 to 2010, 137 had pluvial flooding more than 3 times, and 57 of them had the maximum flooding time more than 12 h. Rainstorm is the most direct driver of urban pluvial flooding [6,16], and climate change is directly responsible for global and regional changes in rainstorm.…”
Section: Impact Of Climate Change On Urban Pluvial Flooding Processes...mentioning
confidence: 99%
See 3 more Smart Citations
“…According to the 2006-2018 China Water and Drought Disaster Bulletin statistics [13], China has been flooded in more than 100 cities every year since 2006, including 258 cities flooded in 2010, 184 in 2012, and 234 in 2013. According to the special research on 351 cities by the Ministry of Housing and Urban-Rural Development of the People's Republic of China [15], 62% of the cities in China had pluvial flooding from 2008 to 2010, 137 had pluvial flooding more than 3 times, and 57 of them had the maximum flooding time more than 12 h. Rainstorm is the most direct driver of urban pluvial flooding [6,16], and climate change is directly responsible for global and regional changes in rainstorm.…”
Section: Impact Of Climate Change On Urban Pluvial Flooding Processes...mentioning
confidence: 99%
“…Many scholars have analyzed the spatial and temporal evolution characteristics of extreme precipitation or rainstorm in China and the causes of the changes [6,7,33,[38][39][40]. Studies have shown that the rainstorm events in the North China Plain are more random during the past few decades [10,15,16], with the maximum rainfall historically occurring much higher than the common heavy rainfall in the North China Plain [17].…”
Section: Impact Of Climate Change On Urban Pluvial Flooding Processes...mentioning
confidence: 99%
See 2 more Smart Citations
“…Urban flooding poses a great threat to societal and personal safety annually. Therefore, the governance of urban flooding is an urgent problem faced by urban development, and its governance and transformation have become hot topics of current urban research (Kong et al 2021). In previous studies, six different years (1966, 1971, 1976, 1981, 1986, and 2000) and six simulated land use scenarios (0%, 20%, 40%, 60%, 80%, and 100% impervious surface areas) were considered to evaluate the impact of urbanization on changes in urban flood risks in coupled hydrological and hydraulic models (Feng et al 2021).…”
Section: Introductionmentioning
confidence: 99%